Growth and properties of Cu3SbS4 thin films prepared by a two-stage process for solar cell applications. Issue 6 (15th April 2017) - Chalapathi, U.; Poornaprakash, B.; Park, Si-Hyun
Abstract: Cu3 SbS4 is a promising material for thin film heterojunction solar cells owing to its suitable optical and electrical properties. In this paper, we report the preparation of Cu3 SbS4 thin films by annealing the Sb2 S3 /CuS stacks, produced by chemical bath deposition, in a graphite box held at different temperatures. The influence of annealing temperature on the growth and properties of these films is investigated. These films are systematically analyzed by evaluating their structural, microstructural, optical and electrical properties using suitable characterization techniques. X-ray diffraction analysis showed that these films exhibit tetragonal crystal structure with the lattice parameters a=0.537 nm and b=1.087 nm. Their crystallite size increases with increasing annealing temperature of the stacks. Raman spectroscopy analysis of these films exhibited modes at 132, 247, 273, 317, 344, 358 and 635 cm −1 due to Cu3 SbS4 phase. X-ray photoelectron spectroscopy analysis revealed that the films prepared by annealing the stack at 350 °C exhibit a Cu-poor and Sb-rich composition with +1, +5 and −2 oxidation states of Cu, Sb and S, respectively. Morphological studies showed an improvement in the grain size of the films on increasing the annealing temperature. The direct optical band gap of these films was in the range of 0.82–0.85 eV. Hall measurements showed that the films are p-type in nature and their electrical resistivity, hole mobility and hole concentration are in the ranges of 0.14–1.20 Ω-cm, 0.05–2.11 cm 2 V −1 s −1 and 9.4×10 20 –1.4×10 19 cm −3, respectively. These structural, morphological, optical and electrical properties suggest that Cu3 SbS4 could be used as an absorber layer for bottom cell in multi-junction solar cells.